A systematic review of the outcomes of osteoporotic fracture patients after hospital discharge: morbidity, subsequent fractures, and mortality - Nazrun AS; Tzar MN; Mokhtar SA; Mohamed IN (Dove Medical Press, 2014)
Ahmad Shuid Nazrun,1 Mohd Nizam Tzar,2 Sabarul Afian Mokhtar,3 Isa Naina Mohamed1 1Department of Pharmacology, 2Department of Medical Microbiology and Immunology, 3Department of Orthopedic, Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur, Malaysia Purpose: Osteoporotic fracture is the main complication of osteoporosis. The current management is to discharge patients as early as possible so they can get back to their daily activities. Once discharged, there are three main issues relating to morbidity, mortality, and risk of a subsequent fracture that need to be addressed and discussed. Therefore, the aim of this systematic review was to summarize and evaluate the evidence from published literature, to determine the outcome of osteoporotic fracture patients after their hospital discharge.Methods: The MEDLINE and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were searched, using the terms “osteoporosis”, “fracture”, “osteoporotic fracture”, “hip fracture”, and “vertebral fracture”. We included only human studies published in English between 2004 and 2014. The reference lists of included studies were thoroughly reviewed in search for other relevant studies.Results: A total of 18 studies met the selection criteria. Most were observational and cohort studies. Out of all the studies, five studies looked into the morbidity, six studies looked into the risk of subsequent fractures, and seven studies looked into mortality. Vertebral fracture caused the greatest health burden, but hip fracture patients were the main users of informal care after hospital discharge. There was an increased risk of a subsequent fracture after a primary fracture compared with the control group, a cohort comparison, or the general population. Osteoporotic fractures, especially hip fractures, are associated with higher mortality rate despite the advances in the management of osteoporotic fracture cases.Conclusion: There is strong evidence to show that after hospital discharge, osteoporotic fracture patients are faced with higher morbidity, subsequent fractures, and mortality. Keywords: osteoporosis; hip fracture, vertebral fracture